Comprehensive analysis of nine m7G-related lncRNAs as prognosis factors in tumor immune microenvironment of hepatocellular carcinoma and experimental validation - Wang, Tao; Zhou, Zhijia; Wang, Xuan; You, Liping; Li, Wenxuan; Zheng, Chao; Zhang, Jinghao; Wang, Lingtai; Kong, Xiaoni; Gao, Yueqiu; Sun, Xuehua (Frontiers in Genetics, 2022)
Background Hepatocellular carcinoma (HCC) remains the most prevalent gastrointestinal malignancy worldwide, with robust drug resistance to therapy. N7-methylguanosine (m7G) mRNA modification has been significantly related to massive human diseases. Considering the unknown m7G-modified LncRNAs in the HCC progression, the study aims at investigating a prognostic signature to improve clinical outcomes and benefit from this for patients with HCC. Methods Two independent databases(TCGA and ICGC) allow us to analyze RNAseq data of HCC patients. First, co-expression analysis was applied to obtain the m7G regulator related lncRNAs.Moreover, consensus clustering analysis was employed to divide HCC patients into Clusters. Then, using Lasso-Cox analysis, the m7G-related lncRNA prognostic signature (m7G-LPS) was first tested in the training set and then confirmed both in the testing and ICGC set. The m7G-LPS could divide HCC patients into two different risk groups(high-risk and low-risk) with the optimal risk score. Then, Kaplan-Meier curves, tumor mutation burden (TMB), therapeutic effects of chemotherapeutic agents, and expressions of immune checkpoints were performed to further enhance the availability of immunotherapeutic treatments for HCC patients. Results A complete of 1465 lncRNAs associated with the m7G genes were finally selected from the TCGA dataset, and through the univariate Cox regression, the expression levels of 22 m7G-lncRNAs were concerning HCC patients’ overall survival cycle length. Then, the whole patients were grouped into three subgroups, and the Cluster1s’ survival rate was longer than that for patients in Cluster2 and Cluster3. Further, nine prognostic m7G-relevant lncRNAs were identified to conduct the m7GLPS, which were further verified by survival analysis, PCA, and receiver operating characteristic(ROC)curve. A prognostic nomogram combined age, grade, gender, stage and m7G-LPS showed strong reliability and accuracy in predicting survival in HCC patients. Finally, immune checkpoints expression, TMB, and several chemotherapeutic agents were remarkably associated with risk scores. More importantly, the OS of the high TMB patients was the worst among another three groups. Conclusion The prognostic model we established is validated by abundant algorithms, which provided a new perspective on HCC tumorigenesis and thus improved individualized treatments for patients.